Akbar : The Mighty Emperor - Mandana, Kavitha (UK Puffin Books, 2010)
On the life of Akbar, 1542-1605, Emperor of Hindustan.
Keywords: India -- India--Mogul Empire -- Akbar, Emperor of Hindustan, 1542-1605